The 2 Meeting of National Control Laboratories for Vaccines and Biologicals in the Western Pacific - Hokyung Oh; Jinho Shin; Chung Keel Lee; Masaki Ochiai; Kiyoko Nojima; Chang Kweng Lim; Sanj Raut; Irene Lisovsky; Stella Williams; Ki Young Yoo; Dong-Yeop Shin; Manabu Ato; et al. (Osong public health and research perspectives, 2018)
The Second Meeting of the National Control Laboratories for Vaccines and Biologicals in the Western Pacific, was jointly organized by the National Institute of Food and Drug Safety Evaluation of the Ministry of Food and Drug Safety in the Republic of Korea, and by the World Health Organization Regional Office for the Western Pacific. In the National Lot Release Systems session countries including Canada, China, Japan, Malaysia, Vietnam, and the Republic of Korea, all shared information on their current Lot Release Systems, including current practices and developments in risk-based official lot release of vaccines. In the session on Quality Control of Blood Products, experts from the National Institute for Biological Standards and Control shared quality control and research results for; blood coagulation factor VIII products, and the measurement of procoagulant activity in immunoglobulin products. Representatives from Japan proposed a regional collaborative study to test aggregated immunoglobulin free from complement activity. A cell-based Japanese encephalitis vaccine potency assay was proposed by representatives from Korea and they also called for voluntary participation of other National Control Laboratories in a collaborative study, on the first Korean Gloydius anti-venom standard. Participants agreed in general to continue communicating, and coordinate presentation of the study results.